Benzyl 3-(2-methylphenyl)dithiocarbazate. - Tayamon, Shahedeh; Begum, Thahira; Mohamed Tahir, Mohamed Ibrahim; Crouse, Karen Anne; Tiekink, Edward R. T. (International Union of Crystallography, 2012)
In the title compound, C15H16N2S2, the central C2N2S2 unit is essentially planar (r.m.s. deviation = 0.047 Å) and forms dihedral angles of 68.26 (4) and 65.99 (4)° with the phenyl and benzene rings, respectively, indicating a twisted molecule. Supramolecular chains with a step topology and propagating along [100] feature in the crystal packing, mediated through N—H(...)S hydrogen bonds. The chains are consolidated into a three-dimensional architecture by C—H(...)π interactions.